Korelasi Perencanaan Pajak, Akuntansi Pertanggungjawaban Dan Komitmen Organisasi Pada Kinerja Manajerial - Ratnawati, Juli; T.A.H, Natalistyo; Dian Andika, Arditya (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
The article  aims to analyze the correlation of tax planning and responsibility accounting on manager performance with the organizational commitment as an intervening variable. The respondents of this study are all levels of managers, both operational and middle level managers at PT. Sinar Sosro Central Java Region as many as 56 people. We use path anaysis to  analyze the data. The study finds that tax planning and responsibility accounting have an influence on organizational commitment. Beeside, tax planning, responsibility accounting and organizational commitment influence toward managerial performance. However, tax planning and accountability accounting do not affect managerial performance through organizational commitment.